2014
DOI: 10.1097/cad.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

20-(s)-Ginsenoside Rg3 induces apoptotic cell death in human leukemic U937 and HL-60 cells through PI3K/Akt pathways

Abstract: Leukemia is currently one of the most deadly diseases. Ginseng has been used in Asian countries for the treatment and prevention of various diseases, including leukemia, but the molecular mechanism of its antileukemia activity has not been well defined. The aim of this study was to explore the effect of 20-(s)-ginsenoside Rg3 on apoptosis in human leukemic U937 and HL-60 cells and the underlying mechanism. We found that 20-(s)-ginsenoside Rg3 reduced cell viability and induced apoptosis in U937 and HL-60 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In recent years, the drugs which target autophagy pathway demonstrate promoting the autophagic death of tumor cells or inhibiting the autophagic protection in order to eliminate tumor cells and resistance to chemotherapy, which overcome the tumor problems and bringing a glimmer of hope in cancer therapy [ 42 ]. On the other hand, many studies have reported that 20(S)-GRh2 has a significant apoptosis effect for K562 and U937cells [ 19 , 20 , 21 , 43 , 44 , 45 ]. Nevertheless, the autophagy that is induced by 20(S)-GRh2 in K562 and U937 cells, and the difference between the two cells to the 20(S)-GRh2 induced apoptosis was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the drugs which target autophagy pathway demonstrate promoting the autophagic death of tumor cells or inhibiting the autophagic protection in order to eliminate tumor cells and resistance to chemotherapy, which overcome the tumor problems and bringing a glimmer of hope in cancer therapy [ 42 ]. On the other hand, many studies have reported that 20(S)-GRh2 has a significant apoptosis effect for K562 and U937cells [ 19 , 20 , 21 , 43 , 44 , 45 ]. Nevertheless, the autophagy that is induced by 20(S)-GRh2 in K562 and U937 cells, and the difference between the two cells to the 20(S)-GRh2 induced apoptosis was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is identified to be the main active component with anticancer effects on human gastric cancer AGS cells, while 20(R)-Rg 3 has no effect ( Park et al, 2014 ). Moreover, 20(S)-Rg 3 is also found to be effective in other cell lines, such as human leukemic U937 and HL-60 cells ( Qiu et al, 2014 ), multiple myeloma U266 cells ( Song et al, 2014a ), human ovarian cancer HO-8910 ( Wang et al, 2014 ) and A2780 cells ( Park et al, 2016 ), and colon cancer HT-29 cells ( Yuan et al, 2010 ).…”
Section: Pharmacologymentioning
confidence: 99%
“…Ginsenoside Rg3 demonstrates therapeutic effects in vitro and/or in vivo against various tumors, including leukemia [22], lung cancer [23], esophageal carcinoma [24], gastric cancer [25], colon cancer [26,27,28], hepatoma [29,30], renal cancer [31], bladder cancer [32], breast cancer [33], ovarian cancer [34], prostate cancer [35,36] and melanoma [37,38,39]. Moreover, combination therapy of ginsenoside Rg3 with other chemotherapeutic agents has also become the focus of recent research.…”
Section: Triterpenoid Saponinsmentioning
confidence: 99%